SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMP IT - Asep Supriadi; Cipto Handoko; Sunarto (UNISAN JURNAL, 2022)
This research was conducted with the aim of academic supervision in improving the quality of learning. This study uses a descriptive qualitative approach, that is, researchers only describe, analyze phenomena, events and activities carried out related to academic supervision carried out by the head of MTs Nurul Hidayah Cilipung, Tulang Bawang Barat Regency with data collection techniques through: Observation, In-depth Interview, and Documentation Studies. As for the selection of research informants, using a purposive technique combined with Snowball Sampling. The data collected through the three techniques were then checked for validity by triangulation. Then analyzed by: (1) data reduction, (2) data presentation and (3) drawing conclusions. Based on the results of the study, the following findings can be concluded: (1) The academic supervision program for the principal of MTs Nurul Hidayah Cilipung Regency was compiled based on the results of the analysis of supervision and monitoring of the previous learning process; The principal’s academic supervision program is prepared at the beginning of the school year, by first identifying problems, determining goals and determining the time of implementation, involving the vice principal of curriculum, vice principal of quality assurance, and teachers; and carried out systematically, (2) the strategy for implementing the principal’s academic supervision includes: supervising learning devices, supervision with class visit techniques, and observing teacher activities in class, and implementing follow-up on the results of academic supervision in the form of personal and group coaching. (3) The implications of the principal’s academic supervision are: (a) Increased ability of teachers in preparing learning tools (b) Increased ability of teachers in carrying out the learning process, (c) Increased ability of teachers in evaluating student learning outcomes. Conclusion: academic supervision is one way to increase teacher professionalism in planning, implementing the learning process and evaluating student learning outcomes in order to improve the quality of learning so that educational goals both locally and nationally can be achieved well.